Implementasi Pelatihan Manajemen Berbasis Sekolah bagi Tenaga Pendidik PAUD Mutiara Bunda - Marswandi, Ega Dwi Putri; Rina Komala; Layali Ihyani; Febria Nurmelia Marlina (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
This community service aims to implement the SBM concept at the Mutiara Bunda PAUD Institution through training, coaching and mentoring activities. The method used is Participatory Action Research (PAR) combined with outcome-based evaluation (OBE) and the CIPP (context, input, process, product) model. The results of the activity show that managers and teachers' understanding of the SBM concept has increased significantly. The institution succeeded in compiling important documents such as the miso vision, annual work plan, organizational structure and simple financial reporting. The conclusion of this activity is that a participatory and action-based approach has proven effective in encouraging the institutional independence of Mutiara Bunda PAUD and creating transparent, accountable and sustainable governance. This model has the potential to be replicated at the Mutiara Bunda PAUD Institution with a similar contextual approach.